Ambition and Self-Actualization of Modern Women in The Queen’s Gambit: A Hierarchy of Needs Perspective - Malika Putri, Nadya; Suryadi, M.; Widyatwati, Ken; Rinjani, Annisa (Universitas Cokroaminoto Palopo, 2025)
This study examines the ambition of the main female character, Beth Harmon, in The Queen's Gambit series through Abraham Maslow's hierarchy of needs theory. This study analyzes how the main character's journey reflects the fulfillment of five levels of human needs: physiological, safety, love and belonging, esteem, and self-actualization. This study contributes to broadening the insight into modern women's ambitions through the representation of fictional characters in popular media. The method used is descriptive-qualitative with a character analysis and narrative approach. Data are analyzed based on the psychological development of the character and the social challenges she faces in the male-dominated chess world. Each level of need shows complex emotional and social dynamics. Beth successfully demonstrates perseverance, courage, and a competitive spirit that reflect women's ambition today in pursuing education and careers amidst gender challenges. This study found that modern women's ambitions relate to achievement and seeking identity and recognition in social and professional spaces.